Immediate Loading Implant Dentistry Strategies Have Their Origins in Periodontal Prosthesis. Issue 2 (1st May 2013) - Ganeles, Jeffrey; Rose, Louis F.; Norkin, Frederic J.; Zfaz, Samuel
Abstract : Introduction: The principles of periodontal prosthesis developed in the 1950s to 1970s by Drs. Amsterdam, Abrams, and Weisgold and explained in Periodontal Therapy, edited by Drs. Goldman and Cohen, provide relevant diagnostic and therapeutic criteria and guidelines that apply to teeth as well as implants. For these situations, occlusal, restorative, surgical, esthetic, biomaterial, pharmacologic, and psychologic skills must be carefully combined for optimal results. These points are illustrated through a case presentation of a challenging patient. Case Presentation: A 62‐year‐old woman presented to her general dentist with a chief complaint of drifting of her recent maxillary anterior restorations. On further questioning, she also complained about pain of these teeth, bilateral temporomandibular muscle pain, and tooth mobility. A treatment plan was developed in conjunction with the patient's restorative dentist to restore the patient to first‐molar occlusion using implants in the maxillary arch and a combination of teeth and implants in the mandibular arch. Conclusion: Combining the guidelines of periodontal prosthesis with state‐of‐the‐art implant dentistry can lead to predictable, beneficial, and efficient treatment, even for the most difficult patients and circumstances.